Predictors of organizational resilience by factorial analysis - Noriega, Salvador (2019)
The global economy is characterized by a progressive complexity, uncertainty, and volatility, which exert intense pressures to organizations and confronts them, with increasing frequency, to disruptive and unexpected events. In such environments, some organizations develop a resilience profile to increase the capacity to anticipate, adapt, and recover equilibrium or even, gain a new advantage position after the disruption. In this research, the factors of organizational resilience (OR) are identified and a structural equations model is developed. The article discusses the theoretical background and the literature of the resilience factors, and proposes their classification, which is used for the development of a questionnaire for the determination of the relative importance of the factors in several industrial sectors. The internal consistency of the questionnaire was validated with the Cronbach’s a coefficient and was applied to a sample of 159 manufacturing companies of the twin plant “maquiladora” industry of Ciudad Juarez, Mexico, using a convenience sampling method. The key driver factors related to ´ the development of OR are identified employing a partial least squares structural equation modeling approach, also is developed a structural model as a predictor of OR and its effectiveness, covering the description of the proposed model. By hypotheses tests, it is verified that resilient leadership explains the role of variables related to the development of OR, having a high influence in the organizational culture and in the capacity to organize and manage operations, being these three contributors, the drivers of the adaptation capacity that has a direct relation to the development of resilience